Development of cosmos caudatus (Ulam Raja)-enriched beef burger. - Mat Easa, Azhar
An Ulam Raja Extract with the highest yield and showed a high ORAC value was prepared. This has been code-named "UREXl". UREXI has been added into beef burger and subjected to a frozen storage.The extract showed good protection ability against fat oxidation that was as Good as a commercial green tea extract. Thus, it is possible to produce Cosmos caudatus (Ulam Raja)-enriched beef burger